Entrepreneurial ecosystem: do you trust or distrust?. Issue 2 (14th May 2018) - Muldoon, Jeffrey; Bauman, Antonina; Lucy, Carol
Abstract : Purpose: The purpose of the paper is to examine the role of trust and distrust in social networks within the entrepreneurial ecosystem and to develop a conceptual scheme of the impact of trust and distrust on productive and unproductive entrepreneurship. Design/methodology/approach: This study develops a conceptual scheme, founded on the social capital and resource-based view of a firm, by exploring the impact of trust and distrust on entrepreneurial behavior in a social network. Findings: As the paper indicates, trust within an entrepreneurial ecosystem has a positive impact on productive entrepreneurship, while distrust within the ecosystem is expected to be unproductive and destructive (or potentially illegal) to an economy. Research limitations/implications: The research implication of this paper is that it connects levels of trust and distrust within the ecosystem to the type of the behavior exhibited by entrepreneurs leading either to productive or unproductive entrepreneurial endeavors. As this study is based on the theoretical review resulting in a conceptual scheme, it requires further investigation of proposed interactions. Practical implications: This paper offers strategic alternatives for entrepreneurs seeking to enhance future endeavors by strengthening trust within social networks for the mutual benefits of the ecosystem and businesses within it. Social implications: This study highlights the importance of two social constructs of trust and distrust in maintaining existing and developing future ecosystems. It also reviews potential outcomes of entrepreneurial behavior and their impact on economies. Originality/value: This research examines both trust and distrust (two separate social constructs) as significant predictors of future outcomes in the entrepreneurial ecosystem that go beyond productive entrepreneurship.